Genetic Evidence for the Physiological Significance of the d-Tagatose 6-Phosphate Pathway of Lactose and d-Galactose Degradation in Staphylococcus aureus - Bissett, Donald L. (1974)
Mutants of Staphylococcus aureus were isolated which were unable to utilize d-galactose or lactose, but which were able to utilize all other carbohydrates tested. Growth of the mutants on a peptone-containing medium was inhibited by d-galactose. Of those mutants selected for further study, one (tagI2) was missing d-galactose 6-phosphate isomerase, one (tagK3) was missing d-tagatose 6-phosphate kinase, and one (tagA4) was missing d-tagatose 1, 6-diphosphate aldolase. Each of these mutants accumulated the substrate of the missing enzyme intracellularly. Spontaneous revertants of each of the mutants simultaneously regained their ability to utilize d-galactose and lactose, lost their sensitivity to d-galactose, regained the missing enzymatic activities, and no longer accumulated intermediates of the d-tagatose 6-phosphate pathway. These data support our previous contention that the physiologically significant route for the metabolism of d-galactose and the d-galactosyl moiety of lactose in S. aureus is the d-tagatose 6-phosphate pathway. Furthermore, a mutant constitutive for all three enzymes of this pathway was isolated, indicating that the products of the tagI, tagK, and tagA genes are under common genetic control. This conclusion was supported by the demonstration that d-galactose 6-phosphate isomerase, d-tagatose 6-phosphate kinase, and d-tagatose 1, 6-diphosphate aldolase are coordinately induced in the parental strain.